Cooperação social: uma abordagem neocontratualista - Borile Júnior, Eduardo (My University, 2020)
From the hypothesis that social cooperation is not based on Levinasian altruism and refuting the exclusive necessity of duty for its realization, it is conjectured that the act of cooperating distances itself from the supposed morality once considered. To this end, social cooperation is analysed through the lens of Thomas Hobbes's contractualism (1588-1679) and John Rawls's neocontractualism (1921-2002). The Hobbesian conception argues for cooperation when it argues that the three natural causes of human discord are (i) competition, (ii) distrust; and (iii) the glory. In the Rawlsian conception, in turn, it is the principles of the basic structure that constitute the original agreement and will determine the manifestation of social cooperation. It is hypothesized, therefore, that the absence of self-interested moral motivations can weaken cooperative bonds, since, for no reason to cooperate, such an agent hardly cooperates.
A partir da hipótese de a cooperação social não estar sustentada no altruísmo levinasiano e refutando a necessidade exclusiva do dever para a efetivação da mesma, conjectura-se que o ato de cooperar distancia-se da suposta moralidade antes cogitada. Para tal, analisa-se a cooperação social pelas lentes do contratualismo de Thomas Hobbes (1588-1679) e do neocontratualismo de John Rawls (1921-2002). A concepção hobbesiana argumenta em favor da cooperação social quando defende que as três causas naturais da discórdia humana são (i) a competição; (ii) a desconfiança; e (iii) a glória. Por sua vez, na concepção rawlsiana, são os princípios da estrutura básica que constituem o acordo original e vão determinar a manifestação da cooperação social. Hipotetiza-se, portanto, que a ausência de motivações morais autointeressadas pode enfraquecer os vínculos cooperativos, visto que, sem nenhuma razão para cooperar, dificilmente tal agente coopera.
Keywords: Altruísmo; Cooperação - Aspectos morais e éticos; Ética; Filosofia; Altruism; Cooperativeness - Moral and ethical aspects; Ethics; Philosophy